Tuberculous Meningitis: The Important Role of Imaging - Ana Pereira Lemos (Sociedade Portuguesa de Pediatria, 2021)
Tuberculous meningitis is the most severe form of tuberculosis and the diagnosis continues to be challenging for clinicians. Indeed, many cases of Tuberculous meningitis cannot be confirmed based on clinical findings and laboratory techniques are largely insensitive or slow. Clinical presentation can be nonspecific and suggest alternative conditions. The difficulty in diagnosis often leads to a delay in treatment and subsequent mortality.